(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article is the result of research carried out during 2019 and 2020 on the documentation of Espírito Santo cultural devices. In this sense, making a survey, through a bibliographic search and the narratives of the subjects that occupy the cultural facilities of Grande Vitória – ES/BRASIL, is the objective of this text. It also analyzes the relevance of these equipments (museums, galleries and homespaces) when understanding them as spaces aimed at teacher and student training, as well as the locus for artists/researchers/teachers to be inspired, create, research, produce and exhibit their work enhancing local artistic-cultural and educational production. Reflects on educational actions through the educational materials produced in these spaces and their applicability to/in educational institutions. Therefore, it is theoretically based on the studies of Bakhtin (2006), Moreira and Candau (2008), Gabre (2019), Irwin (2008) and Canton (2009). He concludes by proposing, from the dialogue between Art and Education, the relevance of these equipments for the aesthetic-cultural-educational formation of the Espírito Santo population.